Reinstatement and lectotypification of Leea cumingii (Leeaceae, Vitales), a narrow endemic species to the Philippines - Athalappil, Amrutha; Wen, Jun; Molina, Jeanmaire E.; Pradeep, Ayilliath Kuttiyeri (Phytotaxa, 2026)
Leea is a small group of plants belonging to the family Leeaceae (Vitales) with a wide distribution in the Old World tropics. Several species within this genus have been broadly circumscribed, making them species complexes. One of these complexes includes Leea guineensis, a red-flowered species, resulting in more than 30 synonyms across Africa and Southeast Asia. Leea cumingii described from the Philippines has long been considered a synonym of L. guineensis. However, a thorough analysis of the protologue, type specimen, and other herbarium materials revealed that this species is distinct and is therefore reinstated here. The present study provides the description, distribution map, photo plates, and assessment of the conservation status of L. cumingii. In addition, a lectotype is designated for the name, L. cumingii, to stabilize its nomenclatural status.